2022
DOI: 10.3390/life12101518
|View full text |Cite
|
Sign up to set email alerts
|

Switching from Adalimumab Originator to Biosimilar in Patients with Hidradenitis Suppurativa Results in Losses of Response—Data from the German HS Registry HSBest

Abstract: Since 2021, adalimumab biosimilar ABP 501 can be used alternatively to adalimumab originator (ADAO) in the treatment of hidradenitis suppurativa (HS). Effectiveness and safety data remain scarce. We investigated the impact of switching from ADAO to ABP 501 on disease severity and the occurrence of adverse events (AEs) in patients with HS. We analyzed clinical data on patients enrolled in the German HSBest registry. Evaluation outcomes were assessed at three time points (baseline of originator (t0), prior to sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…For instance, the results of the retrospective study carried out by Burlando M et al [21] on 326 HS patients reported a greater loss of effectiveness among patients allocated in the biosimilar group vs. those in the originator group (IRR = 2.2; 95% CI 1.5-3.2, p < 0.001). The registry-based study carried out by Kirsten N et al [22] among 94 HS patients highlighted that 33% of them experienced AEs or loss of efficacy after switching, and that significant differences at the time of switch and 12-14 weeks after the switch were identified for the IHS4 score (p < 0.001) in both groups of patients (with and without loss of efficacy). Similarly, Montero-Vilchez T et al [23] reported that, out of 17 HS patients who switched from the adalimumab originator to the biosimilar for no medical reasons, 10 patients reported severe pain at the injection site and loss of HiSCR response.…”
Section: Main Outcomes Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the results of the retrospective study carried out by Burlando M et al [21] on 326 HS patients reported a greater loss of effectiveness among patients allocated in the biosimilar group vs. those in the originator group (IRR = 2.2; 95% CI 1.5-3.2, p < 0.001). The registry-based study carried out by Kirsten N et al [22] among 94 HS patients highlighted that 33% of them experienced AEs or loss of efficacy after switching, and that significant differences at the time of switch and 12-14 weeks after the switch were identified for the IHS4 score (p < 0.001) in both groups of patients (with and without loss of efficacy). Similarly, Montero-Vilchez T et al [23] reported that, out of 17 HS patients who switched from the adalimumab originator to the biosimilar for no medical reasons, 10 patients reported severe pain at the injection site and loss of HiSCR response.…”
Section: Main Outcomes Main Resultsmentioning
confidence: 99%
“…Fourteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25]49] evaluated the effects in terms of the efficacy and safety derived from the switch among adalimumab products. All studies were carried out in Europe (10/14 in Italy).…”
Section: Adalimumab Switching Studiesmentioning
confidence: 99%
“…The switch from the adalimumab originator to biosimilars, taking medical aspects into account, has now been sufficiently analyzed. [163][164][165][166] In well-controlled patients, the switch from the adalimumab originator to a biosimilar might create problems with respect to effectiveness and compliance. Therefore, the therapy change of patients in remission maintenance therapy is viewed critically.…”
Section: Adalimumab Biosimilarsmentioning
confidence: 99%
“…However, a loss of treatment efficacy has been observed after switching from adalimumab originator to biosimilars in clinical studies [ 124 , 125 , 126 ]. Kirsten et al evaluated the clinical responses of 94 patients after switching from adalimumab originator to biosimilar ABP 501, and reported a loss of response or new onset of adverse events in 33.3% [ 127 ]. Another retrospective cohort study observed a more rapid loss of efficacy in patients taking adalimumab biosimilars compared to the originator agent and additionally found a greater risk for loss of efficacy in switchers compared to non-switchers, suggesting that, in the management of HS, treatment should begin and continue with the same drug [ 128 ].…”
Section: Treatmentmentioning
confidence: 99%